An Overview on Saudi Health Care System - Albeshr , Abdulhameed G.; Alhabdan , Yazeed A. (Research Highlights in Disease and Health Research Vol. 8, 2023)
This review focus on health care system in Saudi Arabia from general view and the challenges opposing the Saudi health care system. Healthcare services had been one of the great priorities of the Saudi Arabian government. In its attempt to improve health services, the Saudi government has invested heavily in the health care sector. By responding to the demands of its citizens the Saudi health system introduced various changes over the years to implement achievement. This leads to improvement of Saudi population health in the recent decades. Mass gathering in religious events face important public health challenges like the transmission of infectious diseases, exacerbation of non-communicable diseases, and disorders related to climate change. With the ultimate goal of providing free and accessible healthcare services for every Saudi citizen and expatriate working in the public sector, the Saudi Arabian government has committed enormous resources to enhancing health care.